Cellular and Molecular Characteristics of Scarless versus Fibrotic Wound Healing - Latha Satish; Sandeep Kathju (Dermatology Research and Practice)
The purpose of this paper is to compare and contrast the discrete biology differentiating fetal wound repair from its adult counterpart. Integumentary wound healing in mammalian fetuses is essentially different from wound healing in adult skin. Adult (postnatal) skin wound healing is a complex and well-orchestrated process spurred by attendant inflammation that leads to wound closure with scar formation. In contrast, fetal wound repair occurs with minimal inflammation, faster re-epithelialization, and without the accumulation of scar. Although research into scarless healing began decades ago, the critical molecular mechanisms driving the process of regenerative fetal healing remain uncertain. Understanding the molecular and cellular events during regenerative healing may provide clues that one day enable us to modulate adult wound healing and consequently reduce scarring.